2017
DOI: 10.14260/jemds/2017/1122
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Various Bulk Fill Composite Resin in Endodontically Treated Class I Premolar (An in-Vitro Study)

Abstract: BACKGROUNDEndodontically treated teeth are more susceptible to fracture as a result of increased brittleness and are weakened because of coronal destruction. Endodontically treated teeth with small or minimal cavities can be restored with direct composites in the presence of buccal and palatal cusp with intact marginal ridge. Bulk fill has minimal polymerisation shrinkage rate, curing depth of 4 mm, better bond strength and good physical properties. Other advantages include fewer void in the restorative materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…But Farahanny et al found that the maxillary premolar teeth that had been endodontically treated with final restoration resin composite bulk-fill had high fracture resistance. 12 Difficulties in looking for study samples of recently extracted upper premolar teeth were also of influence when measuring fracture resistance because tooth that has been extracted quite a while would undergo structural changes. Inorganic materials such as calcium hydroxyapatite and organic materials such as collagen start to deteriorate after the tooth was extracted.…”
Section: Fig 1: Mod Class II Preparation Design On Premolar Teeth 8 Discussionmentioning
confidence: 99%
“…But Farahanny et al found that the maxillary premolar teeth that had been endodontically treated with final restoration resin composite bulk-fill had high fracture resistance. 12 Difficulties in looking for study samples of recently extracted upper premolar teeth were also of influence when measuring fracture resistance because tooth that has been extracted quite a while would undergo structural changes. Inorganic materials such as calcium hydroxyapatite and organic materials such as collagen start to deteriorate after the tooth was extracted.…”
Section: Fig 1: Mod Class II Preparation Design On Premolar Teeth 8 Discussionmentioning
confidence: 99%
“…SDR is a bulk fill composite that can be applied into cavities with a thickness of 4 mm, reduces porosity, and provides a restoration with better consistency. 27 According to Leprince et al SDR has better marginal adaptation 28 and micro tensile than a conventional hybrid composite resin. 2 Micro orifice barrier leakage can cause gutta percha and a sealer to be exposed to saliva and bacteria, so it is necessary to choose a sealer that has good adhesion to the tooth structure to prevent bacterial and salivary contamination into the root canal.…”
Section: Discussionmentioning
confidence: 99%